Higher intensity walking improves global cognition during inpatient rehabilitation: a secondary analysis of a randomized control trial - Peters, Sue; Lohse, Keith R.; Klassen, Tara D.; Liu-Ambrose, Teresa; Dukelow, Sean P.; Bayley, Mark T.; Hill, Michael D.; Pooyania, Sepideh; Yao, Jennifer; Eng, Janice J. (Frontiers in Neurology, 2023)
Cognitive deficits are common poststroke. Cognitive rehabilitation is typically used to improve cognitive deficits. It is unknown whether higher doses of exercise to promote motor recovery influence cognitive outcomes. Our recent trial, Determining Optimal Post-Stroke Exercise (DOSE), shows more than double the steps and aerobic minutes can be achieved during inpatient rehabilitation versus usual care, and translates to improved long-term walking outcomes. Thus, the secondary analysis aim was to determine the effect of the DOSE protocol on cognitive outcomes over 1-year poststroke. The DOSE protocol progressively increased step number and aerobic minutes during inpatient stroke rehabilitation over 20 sessions. The Montreal Cognitive Assessment (MoCA), Digit Symbol Substitution Test (DSST), and Trail Making Test B were completed at baseline, post-intervention, and 6- and 12-months poststroke, administered using standardized guidelines. Using the DOSE data, we used mixed-effect spline regression to model participants’ trajectories of cognitive recovery, controlling for relevant covariates. Participants (Usual Care n = 25, DOSE n = 50) were 56.7(11.7) years old, and 27(10) days post stroke. For the MoCA, there were statistically significant Group × Trajectory(p = 0.019), and Group × ΔTrajectory (p = 0.018) interactions with a substantial clinically meaningful difference, from +5.44 points/month improvement of the DOSE group compared to +1.59 points/month improvement with Usual Care during the 4-week intervention. The DSST and Trails B improved over time but were not different between groups. Taking advantage of this early difference may lend support to continued efforts to increase intensity, during and after discharge from inpatient rehabilitation, to improve cognition. Clinical trial registration: www.clinicaltrials.gov, NCT01915368.